Enhancing the success of Ghanaian public road construction projects. Issue 1 (31st December 2023) - Barajei, Chelteau; Kheni, Nongiba A.; Appiah-Kubi, Emmanuel; Danso, Humphrey; Iddrisu, Abdul Wahab
Abstract: The objective of this research paper is to determine the critical success factors (CSFs) influencing the success of public road construction projects from the perspective of a developing nation. A self-administered questionnaire was used to gather data on the extent to which critical success factors gathered from literature impact the success of public road construction projects from sector practitioners' perspectives in Ghana. The data was then analysed using factor analysis. The study revealed that external environmental factors have the highest influence (46.23%) on public road construction project success, followed by project management factors (12.25%) while procurement-related factors have the least impact (6.97%). Public construction project management organisations and the government will now have a deeper understanding of CSFs that influence the success of public construction projects and use them as a guide to enhance the successful delivery of public road construction projects. Even though numerous studies have been undertaken to enhance the success of construction projects in Ghana, very little attention has been given to procurement-related factors. Thus, the study outcome will add value to sector practitioners and the Government of Ghana in the management of public road construction projects.